Why UK doctors should be troubled by female genital mutilation legislation. (June 2017) - Shahvisi, Arianne
A UK doctor was recently acquitted of charges of reinstating a variety of female genital mutilation after delivering a child. In this paper, I contend that this incident reflects a broader confusion concerning the ethico-legal status of non-therapeutic genital surgeries for children and adults, which are not derivable from tenets of medical ethics, but rather violate them. I argue that medical professionals have an obligation to announce and address this confusion in order to motivate legislative reform, since the inconsistency of the current law entrenches the underlying sexism and ethnocentrism upon which its sense depends. Without convincing arguments for (a) condoning male circumcision and female cosmetic genital surgery and for (b) treating adult women of colour as lacking the capacity to consent, the current legislation stands in need of urgent revision.